Proof-of-Lottery: Design for Block Producing Algorithm Based on PoS for Scalability - Lee, Sung Bin; Hwang, Dong Yeop; Kim, Jonghyun; Kim, Ki Hyung (International Conference on Information Networking, 2020)
As blockchain technology has become popular, blockchain services have emerged. Blockchain has the potential to change the industry paradigm. However, decentralized P2P environment of blockchain creates a number of problems. In this paper, we suggest a design for a PoS, block producing algorithm, named Proof-of-Lottery(PoL) to solve these problems. The idea is that selecting block producer in a similar way to drawing a lottery. We expect to improve scalability in blockchain while not hurting decentralization.
Keywords: block producing; decentralization; P2P environment; block producing; blockchain; decentralization; PoS; scalability